Risk factors and economic burden of healthcare-associated infections among patients supported by extracorporeal membrane oxygenation in the ICU: a cohort study from China - Zhenyu Hu; Minjin Peng; Chen Dong; Li Li; Qiao Hu; Hanlin Liao; Haining Jiang; Xianglan Fang; Qifei Zhang; Binbin Fu; Tingyu Lan; Kun Meng; et al. (Antimicrobial Resistance and Infection Control)
Abstract Background Extracorporeal Membrane Oxygenation (ECMO) is a critical life-support technology widely used for managing patients with cardiopulmonary failure. However, ECMO patients are particularly susceptible to healthcare-associated infections (HAIs) due to their critical illness and the invasive procedures. These infections not only reduce patients’ quality of life but also increase healthcare resource utilization. Therefore, understanding the characteristics and risk factors of HAIs in ECMO patients and establishing/implementing targeted preventive strategies are essential. Objective This study aimed to analyze the epidemiological characteristics of HAIs, investigate associated risk factors, and assess the economic impact on patients receiving ECMO support. Methods This cohort study included patients who received ECMO support at Taihe Hospital, Hubei University of Medicine, from February 2017 to September 2023. Patients were categorized into an infection group and a non-infection group based on the occurrence of HAIs. Collected data included basic patient information, infection sites, pathogen distribution, and economic burden. Risk factors for ECMO-related HAIs were analyzed using both univariate and multivariate methods, with statistical significance defined as p < 0.05. Multivariate competing risk regression analysis was performed to identify independent risk factors significantly associated with ECMO-related HAIs. Results The study included 97 eligible ECMO patients, predominantly male (77, 79.38%), with a mean age of 46.7 ± 16.5 years. The total ECMO support duration across all patients was 467.3 days, with a median hospital stay of 12.5 days (range: 4.4–25.5 days). Of note, 86.60% of the patients received venoarterial (VA) ECMO support. Among these patients, 14.43% developed ECMO-related HAIs, resulting in 17 HAI events among 14 patients. These events comprised 10 respiratory tract infections (RTIs), 4 bloodstream infections (BSIs), 2 surgical site infections (SSIs), and 1 urinary tract infection (UTI). The rate of ECMO-related HAIs was 36.4 cases per 1,000 ECMO days. A total of 29 pathogenic microbial strains were identified, including 21 multidrug-resistant bacteria (72.41%; 72.41% Gram-negative, 20.69% Gram-positive), and 2 fungal strains (6.90%). Independent risk factors for ECMO-related HAIs included tracheostomy (odds ratio [OR] = 28.6, p = 0.003) and decreased platelet count (OR = 0.975, p = 0.004). Median total hospitalization expenses were significantly higher in the infection group (US$100,270.4 vs. US$32,108.6; p < 0.05). Conclusions Patients receiving ECMO support are at a heightened risk of developing HAIs, with respiratory tract infections (RTIs) and bloodstream infections (BSIs) being the most prevalent types. The study identified tracheostomy and decreased platelet count as independent risk factors for ECMO-related HAIs. These infections result in prolonged hospital stays and increased economic burden. Therefore, targeted preventive strategies that address these risk factors should be prioritized to reduce infection incidence, aiming to reduce the incidence of infections and alleviate the associated financial burden.